2019
DOI: 10.1177/1724600819881147
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of B7H1 and B7H4 expression in pancreatic cancer: A meta-analysis

Abstract: Objective: The clinical implications of B7H1 and B7H4 in pancreatic cancer have been described however, the prognostic significance of these genes in pancreatic cancer patients remains inconclusive. The aim of the present study was to evaluate the prognostic role of B7H1 and B7H4 in pancreatic cancer patients. Methods: Electronic databases (PubMed, EMBASE, and the Cochrane Library) were searched for relevant articles published before May 2019. Meta-analyses were performed by pooling the hazard ratios (HRs) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Surgical resection is the only curative approach for pancreatic cancer and is feasible in 15% of the cases [ 4 ]. However, even for patients with operable pancreatic cancer, the 5-year survival rate is only 18%–24% [ 5 ]. One of the major reasons for the poor prognosis is the lack of effective biomarkers [ 4 ]; therefore, identification of novel prognostic markers is pivotal for better management of patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is the only curative approach for pancreatic cancer and is feasible in 15% of the cases [ 4 ]. However, even for patients with operable pancreatic cancer, the 5-year survival rate is only 18%–24% [ 5 ]. One of the major reasons for the poor prognosis is the lack of effective biomarkers [ 4 ]; therefore, identification of novel prognostic markers is pivotal for better management of patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, many prognostic factors have been identified and considered, such as hemoglobin level, tumor burden, liver metastases, venous thromboembolism, baseline expression of B7H1 or B7H4, and baseline CA19-9 [17][18][19][20][21][22][23]. One of the most significant prognostic factors is baseline ECOG PS.…”
Section: Introductionmentioning
confidence: 99%
“…120 Recent studies indicated the broad spectrum of patients' tumors that have been associated with aberrant B7-H4 expression across a wide variety of cancers, including colorectal, craniopharyngioma, RCC, BC, prostate cancer, pancreatic cancer, esophageal squamous cell carcinoma (ESCC), and cervical cancer. [137][138][139][140][141][142][143][144] Furthermore, serum sB7-H4 may be a valuable prognostic marker in patients in this wide spectrum of cancers. In patients with non-metastatic ccRCC, the high levels of sB7-H4 along with elevated PB neutrophil count were associated with either poor progression-free survival (PFS) or OS.…”
Section: New B7 Family Checkpoints Moleculesmentioning
confidence: 99%